Lazy home-based protocol for a software distributed shared memory system. (26th May 2009) - Yu, B.H.; Werstein, P.
This paper presents the design and implementation of our novel home-based software Distributed Shared Memory (DSM) system. We call our system Lazy Home-based Scope Consistency (LHScC) since the system implements scope consistency lazily based on the home-based protocol. Our technique is different from others in that an optimum home node is decided before updating a home node. The performance evaluation shows that LHScC is more scalable than other DSM systems and removes the home assignment problem in the usual home-based protocol.